Analysis of factors related to unmet need for family planning in Bantul, D.I. Yogyakarta - Lutfiyati, Afi; Susanti, Dwi (MEDIA ILMU KESEHATAN, 2024)
Background: Unmet need for family planning refers to women who wish to delay or limit births but didn’t use contraceptive methods to achieve them. Factors related were marital status, place of residence, and access to health services. Occupational factors, sources of information, husband’s support for family planning, and discussions about family planning with husbands were also related to unmet need. Objective: To identify that most influence unmet need for family planning in Bantul District, D.I. Yogyakarta.Methods: Research design using a cross-sectional approach with a cluster random sampling technique, namely 331 couples of reproductive age in Wonokromo I and Wonokromo II villages. The research instrument was a questionnaire. The results were analyzed using Chi-square test and multivariate with logistic regression.Results: Chi-square test on variables of knowledge about family planning p=0.406, access to family planning services with p-value=0.005, sources of information p=0.001, discussion of family planning with husbands p=0.001, and husband’s support in family planning with p=0.001. The OR value of discussing contraception with the husband were 6.3.Conclusion: The most dominant factor related to unmet need for family planning in Bantul district, D.I. Yogyakarta were a discussion of family planning with husbands